Mortality and replacement rate of Tellicherry and its crossbred goats in Tamil Nadu - THIRUVENKADANI, A K; KARUNANITHI, K (The Indian Journal of Animal Sciences, 2011)
A study on mortality and replacement rate ofTellicherry and its crossbred goats were made over a period of 16 years with 140 mortality and 449 kidding records. The annual mortality ranged from 2.3 to 30.5% with an average of 14.2%. In general, the young animals up to 3 months (31.5%) and 3-6 months (20.7%) age groups were considered as in the most critical periods. The cause.s of mortality between seasons and sexes were not significant but it was significant between kids and adults. The mortality rate observed in summer, south-west, north-east and winter were 20.7, 35.0, 17.9 and 26.4% respectively. The maximum deaths occurred due to pneumonia (15.7%) followed by enteritis (12.1%) and stomatitis (11.4%). Atotal of33.9% ofthe females left the flock either due to death or culling and sales before first kidding. The replacement rate was 32.3 and 66.1%on total kids born and total female kids born basis respectively. Year of birth, type ofbirth and birth weight offemale kids did not have significant effect on replacement rate. Mortality rate was highest among the female kids having lower birth weight Le.